Social-ecological vulnerability of small-scale farming in the southern Andes: the role of Indigenous and Local Ecological Knowledge in adaptation to climate variability - Rodríguez-Díaz, Paulina; Marchant, Carla; Oyarzo, Camilo; Ibarra, José Tomás (Frontiers in Sustainable Food Systems, 2025)
Small-scale farming is highly vulnerable to climate variability due to the increased uncertainty in production processes caused by short-term changes in precipitation and temperatures. We investigated the key factors behind the social-ecological vulnerability to climate variability of small-scale farming in the southern Chilean Andes. We adopted a mixed methods approach that included climate variability data at the basin level, semi-structured interviews, characterization data sheets and participant observation. The data was analyzed according to three dimensions of vulnerability: exposure, sensitivity and adaptive capacity. Our results reveal the significant interannual variation in accumulated seasonal precipitation and the frequency and intensity of drought events in the basin. Also, we found that small-scale farmers perceive social-ecological vulnerability through the impact on their daily practices and experiences. They view water as a common resource that depends not only on climatic conditions, but also on treatment of the ecosystem that maintains it. We observe that collective adaptation strategies, such as fairs, traditional festivals, and cooperatives organized by small-scale farmers, enhance adaptive capacity by increasing income, which enables investment in equipment, technology, and inputs for adapting production systems to climate variability. We conclude that individual adaptive capacity does not suffice to address the exposures and sensitivities that produce social-ecological vulnerability. It is, therefore, key to design collective adaptation strategies of a local and participatory nature that incorporate Indigenous and Local Ecological Knowledge.